Pathological vascular and inflammatory biomarkers of acute- and chronic-phase traumatic brain injury - Madeleine L Werhane; Nicole D Evangelista; Alexandra L Clark; Scott F Sorg; Katherine J Bangen; My Tran; Dawn M Schiehser; Lisa Delano-Wood (Concussion)
Given the demand for developing objective methods for characterizing traumatic brain injury (TBI), research dedicated to evaluating putative biomarkers has burgeoned over the past decade. Since it is critical to elucidate the underlying pathological processes that underlie the higher diverse outcomes that follow neurotrauma, considerable efforts have been aimed at identifying biomarkers of both the acute- and chronic-phase TBI. Such information is not only critical for helping to elucidate the pathological changes that lead to poor long-term outcomes following TBI but it may also assist in the identification of possible prevention and interventions for individuals who sustain head trauma. In the current review, we discuss the potential role of vascular dysfunction and chronic inflammation in both acute- and chronic-phase TBI, and we also highlight existing studies that have investigated inflammation biomarkers associated with poorer injury outcome.